Afrotropical Limnophora Robineau-Desvoidy (Diptera, Muscidae) with the description of four new species - Couri, Márcia; Pont, Adrian (Zootaxa, 2017)
All the Afrotopical Limnophora Robineau-Desvoidy (Diptera, Muscidae) deposited in the Natural History Museum, London (United Kingdom) were analyzed, including the types of the species described by Emden, mainly from the British Museum (Natural History) Ruwenzori Expedition of 1934–1935. Diagnoses and notes on all the species recorded from the Afrotropical region are given, together with illustrations of the male terminalia (when sufficient material was available), some of which are given for the first time. We made the following taxonomic changes: Limnophora terrestris Paterson, 1955 is a junior synonym of Limnophora translucida Stein, 1913 (syn. nov.); Limnophora aculeipes latilamellata Malloch, 1921 has its status revised and is elevated to species rank (stat. rev.) with Limnophora aculeipes eurymetopa Emden, 1951 proposed as a junior synonym (syn. nov.); L. majuscula kinangopana Emden, 1951 is also raised to species rank (stat. nov.). Four new species are described: Limnophora alta sp. nov.; Limnophora nuda sp. nov.; Limnophora numerosa sp. nov. and Limnophora sinuosa sp. nov., with illustrations of male terminalia.